OBSERVATIONS ON THE FECUNDITY IN FRESHWATER CATFISH MYSTUS BLEEKERI (DAY) FROM HIMAYATHSAGAR, HYDERABAD - PISKA, RAVI SHANKAR; DANIEL, RAJ K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1988)
Fecundity of freshwater catfish, Mystus bleekeri (Day) inhabiting Himayathsagar, Hyderabad was studied. The absolute fecundity ranged from 6822 to 2683 in the fishes measuring from 157 to 244 mm in total length. The relative fecundity was calculated as 848 ova/cm. total length and 537 oval.g. body weight. The mathematical relationships between fecundity and total length, body weight, ovary length and vary weight have been established. The regression values for these relationships were 30935 0 6221, 1 100 and 1.0543 respectively. In all the four cases, linear relationship was found.